Amphotericin B and Fluconazole Affect Cellular Charge, Macrophage Phagocytosis, and Cellular Morphology of Cryptococcus neoformans at Subinhibitory Concentrations - Nosanchuk, Joshua D. (American Society for Microbiology, 1999)
Amphotericin B (AmB) and fluconazole (FLU) are the major antifungal drugs used in the treatment of cryptococcosis. Both drugs are believed to exert their antifungal effects through actions on cell membrane sterols. In this study we investigated whether AmB and FLU had other, more subtle effects on C. neoformans that could contribute to their therapeutic efficacy. C. neoformans cells were grown in media with subinhibitory concentrations of either AmB or FLU and analyzed for cellular charge, phagocytosis by macrophages with antibody and complement opsonins, appearance by scanning electron and light microscopies, and release of the capsular polysaccharide glucuronoxylomannan into the culture medium. Growth in the presence of either AmB or FLU resulted in major reductions in cellular charge, as measured by determination of the zeta potential. Phagocytosis studies demonstrated that exposure of C. neoformans to subinhibitory concentrations of AmB or FLU enhanced phagocytosis by macrophages. Scanning electron microscopy revealed that a large proportion of cells had an altered capsular appearance. Cells grown in medium with either AmB or FLU were smaller and released more glucuronoxylomannan into the culture medium than cells grown without antibiotics. The results suggest additional mechanisms of action for AmB and FLU that may be operative in body compartments where drug levels do not achieve the MICs. Furthermore, the results suggest mechanisms by which AmB and FLU can cooperate with humoral and cellular immune defense systems in controlling C. neoformans infections.